2013
DOI: 10.1515/hf-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Extractives of mechanically wounded wood and knots in beech

Abstract: Various types of wound-associated wood, such as discoloured wood including knots of living and dead branches, were sampled from common beech trees (Fagus sylvatica L.), extracted, and the extracts have been analysed by GC and colourimetry assay. Sequential pressurised solvent extraction was applied with cyclohexane and aqueous methanol. The yield of hydrophilic compounds was three to five times higher than that of lipophilic extractives. The fractions differed mainly in their hydrophilic moieties. The lipophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Extractions were performed in 300 mL Erlenmeyer flasks equipped with a ground glass stopper. Extractions of 6 hours were conducted by the procedures of Albert et al (2003), and Vek et al (2014). Afterwards, the extracts were filtered through Munktell 388 quantitative ashless filter paper (Ahlstrom Munktell).…”
Section: Extraction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Extractions were performed in 300 mL Erlenmeyer flasks equipped with a ground glass stopper. Extractions of 6 hours were conducted by the procedures of Albert et al (2003), and Vek et al (2014). Afterwards, the extracts were filtered through Munktell 388 quantitative ashless filter paper (Ahlstrom Munktell).…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…On the other hand, extractives are of great importance in wood technology; they can affect the successful implantation of hydrothermal wood processing (e.g., wood drying), which is necessary in the production of finished wood products. It has been suggested that extractives, especially polyphenols among others, participate in the colour changes of wood during tree growth (Vek et al 2014(Vek et al , 2015 or wood processing (Burtin et al 1998;Kreber et al 1998;Pervan et al 2006;Esteves et al 2008;Straže et al 2008;SandovalTorres et al 2010;Chen et al 2014;Tolvaj et al 2016). Sundqvist and Morén (2002) concluded that the degradation products of wood polymers and extractives participate in wood colour formation during hydrothermal processing.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of beech wood dust, extracts were characterized by a relatively low amount of lipophilic (Vek et al, 2014). Besides fatty acids, the extracts of beech knots are also characterized by a low concentration of resin acids (Lindberg et al, 2004).…”
Section: Lipofi Lne Ekstraktivne Tvarimentioning
confidence: 99%
“…In addition to simple phenols, the presence of aromatic dimeric structures, i.e. lignin-type compounds, was also proven in beech wood extracts (Koch et al, 2003;Vek et al, 2014). These dimers made up of coniferyl and sinapyl alcohol were referred to as the precursors of a lignin biosynthesis accordingly to Koch et al (2003), but they can represent another group of phenolic extractives, called lignans.…”
Section: Hydrophilic Extractivesmentioning
confidence: 99%
See 1 more Smart Citation